A qualitative investigation of the need for and feasibility of weight loss programs on university campuses. Issue 1 (January 2022) - Bennett, Morgane; Whiteley, Jessica A.; Gu, Jiayan; Gaminian, Azar; Napolitano, Melissa A.
Abstract: Background: Despite the public health significance of overweight and obesity, weight management has remained a low priority for health-related programming on university campuses. Objective: Investigate the need for and feasibility of implementing university-based weight loss programs. Methods: The Practical, Robust Implementation and Sustainability Model (PRISM) was used as a framework. Semi-structured individual interviews were conducted with fifteen university staff and students from two large U.S. universities in the Northeast and Mid-Atlantic. Interviews aimed to assess readiness, preferences, characteristics, barriers and facilitators in each of the four adapted PRISM domains: (1) Organizational and Recipient (Student) Perspectives on the Intervention, (2) Recipient (Student) Characteristics, (3) Internal Environment (organizational characteristics and infrastructure), and (4) External Environment. Verbatim transcriptions were analyzed using inductive and deductive thematic analyses. Themes were extracted as outlined by Consensual Qualitative Research. Results: Participants supported university-based weight loss programs, but recognized barriers of resources, coordination across entities, and competing health issues taking priority for school programming. Campus built environment and students' busy schedules were identified as barriers to maintaining healthy weight and participation in weight loss programs. Recommendations included designing weight loss programming with a positive and holistic approach, minimizing weight-stigma, ensuring support from university leaders and students, and securing external funding. Conclusions: The identified themes provide recommendations for universities looking to develop and implement weight loss programming.